Архівні фонди ДАВО як джерело вивчення нацистської окупаційної політики у сфері освіти (1941–1944 рр.) - Гончаренко, Інна (Видавництво Львівської політехніки, 2015)
The article analyzes the funds and documents that are archived DAVO Ukraine on the theme: "The Nazi occupation policies in education in the territory Reichskommissariat "Ukraine" (1941–1944 gg.)".
Keywords: archival records; politics occupation; vocational training; educational institutions; Reichskommissariat "Ukraine"